Bridging the knowledge gap on mycoses in Africa: Setting up a Pan-African Mycology Working Group - (:unkn) unknown (My University, 2020)
Most African countries have poorly funded and overburdened health systems. Additionally, a high prevalence of HIV in Sub-Saharan Africa contributes to a high burden of opportunistic fungal infections. Data generated by GAFFI from 15 of 57 African countries revealed that an estimated 47 million Africans suffer from fungal diseases, of whom an estimated 1.7 million suffer from a serious fungal infection annually. Almost all African countries lack a surveillance system for fungal infections with the exception of South Africa. South Africa is also the only African country with a national mycology reference laboratory. Across the continent, there is a pervasive picture of inadequate/poor diagnostic capacity, low level of awareness among healthcare workers and policymakers and unavailability and non-accessibility to essential antifungal medications. Recent outreach efforts by the International Society for Human and Animal Mycology (ISHAM) and the European Confederation of Medical Mycology (ECMM) have aimed to increase involvement of African countries and experts in global initiatives such as "One World One Guideline" and also the ECMM Academy. Recently, under the auspices of ISHAM, the African sub-region created a network of mycology experts whose goal is to organise and engage African leaders in the field of medical mycology. The aim of this ISHAM Working Group was to facilitate interaction and synergy among regional leaders in order to develop educational programmes for capacity building to aid in the diagnosis and care of patients with fungal infections in Africa. The working group will also encourage country initiatives to develop clinical guidelines, to support surveys and to support the establishment of reference mycology laboratories.
Keywords: African Research